Exposure to solar ultraviolet radiation and breast cancer risk: A dose-response meta-analysis. Issue 45 (6th November 2020) - Li, Yilun; Ma, Li
Abstract : Abstract: The relationship between solar ultraviolet radiation and the risk of breast cancer is conflicting. The purpose of our study was to quantitatively assess the relationship between solar ultraviolet radiation and breast cancer risk and to analyze related factors such as age and sunscreen use. Articles indexed in PubMed and Embase and published between January 2005 and March 2020 were searched for relevant keywords. The relative risk was calculated using random-effect or fixed-effect models in the meta-analysis and dose-response meta-analysis, which were conducted according to the Meta-Analyses of Observational Studies in Epidemiology reporting guidelines. Sensitivity analyses for heterogeneity and publication bias were evaluated. Six studies were eligible for inclusion in the meta-analysis, and three of these were included in the dose-response analysis. We found a correlation between exposure to solar ultraviolet radiation and breast cancer risk (relative risk: 0.70, 95% confidence interval: 0.65, 0.75). We also found a linear dose-response relationship between the exposure and breast cancer risk (relative risk: 0.86, 95% confidence interval: 0.81, 0.91) in women over 40. Not tanning and covering the limbs were associated with breast cancer risk, but sunscreen use was not. Exposure to solar ultraviolet radiation is negatively correlated with breast cancer risk, and the association is linear in women over 40. This is the first dose-response meta-analysis on the topic, and the influence of factors such as estrogen receptor status, occupational exposure, and ethnicity requires in-depth study. Abstract : Supplemental Digital Content is available in the text